Dipole transitions and Stark effect in the charge-dyon system; Journal of Physics A: Mathematical and Theoretical; Vol. 40, iss. 22 - Mardoyan L. Levon; Nersessian A. P. Armen Petrosovich; Sarkisyan H. Hayk; Yeghikyan V. Vahagn (2007, 2007)
Title screen